ARSITEKTUR POHON BERAKTIVITAS OWA JAWA (Hylobates moloch) HASIL REHABILITASI DI KAWASAN CAGAR ALAM GUNUNG TILU BLOK GAMBOENG CIWIDEY BANDUNG - JAWA BARAT - Anton Hidayatullah; Ana Widiana; Astuti Kusumorini (UIN Sunan Gunung Djati Bandung, 2021)
Primates are forest dwellers that play an important ecological function in helping forest regeneration. The JavanGibbon (Hylobates moloch) is an endemic primate of Java Islandcategorized as Endangered Species by the IUCN. This species is also included in Appendix I by CITES. Gunung Tilu nature reserve located in West Java is one of the rehabilitation sites for the Javan Gibbon. The purpose of this research was to know the daily activities of the Javan Gibbon and the type of tree architecture used by the Javan Gibbon in the Gunung Tilu nature reserve. The research was carried out from January until March 2021 using direct observation (Focal animal sampling) and ad-libitummethods targeting the specific object of Javan Gibbon rehabilitate, namely Lilo. Based on this study, the average time of Lilo's activity was 10 to 11 hours a day starting from 06.00 am until 04.55 pm. The percentages of Lilo's activities were 19% brachiation, 15%feeding, 14% grooming, 14% jumping, 14% resting, 12% climbing,5% play, 5%vocal, 1% urination, and defecation 1%. There were4 architectural models of trees used by Lilo, namely Scarrone, Leeuwenberg, Rauh, and Troll. The trees used by Lilo were composed of 50 species from 7 families.